Genetic analysis of 62 Chinese families with Duchenne muscular dystrophy and strategies of prenatal diagnosis in a single center - Jingjing Zhang; Dingyuan Ma; Gang Liu; Yuguo Wang; An Liu; Li Li; Chunyu Luo; Ping Hu; Zhengfeng Xu (BMC, 2019)
Abstract Background Duchenne muscular dystrophy (DMD) is a severe X-linked recessive neuromuscular disorder. Patients with DMD usually have severe and fatal symptoms, including progressive irreversible muscle weakness and atrophy complicated with gastrocnemius muscle pseudohypertrophy. DMD is caused by mutations in the dystrophin-encoding DMD gene, including large rearrangements and point mutations. This retrospective study was aimed at supplying information on our 4-year clinical experience of DMD genetic and prenatal diagnosis at the Department of Prenatal Diagnosis in Women's Hospital of Nanjing Medical University. Methods Multiplex ligation-dependent probe amplification (MLPA) was used to detect the exon deletions or duplications. And Ion AmpliSeq™ panel for inherited disease was used as the next-generation sequencing (NGS) method to identify the point mutations in exons of DMD gene, but the introns were not sequenced. Results In this study, the large deletions and duplications of DMD gene were detected in 32 (51.6%) of the 62 families, while point mutations were detected in 20 families (32.3%). The remaining 10 families with a negative genetic diagnosis need to be reevaluated for clinical symptoms or be detected by other molecular methods. Notably, six novel mutations were identified, including c.412A > T(p.Lys138*), c.2962delT(p.Ser988Leufs*16), c.6850dupA (p.Ser2284Lysfs*7), c.5139dupA (p.Glu 1714Argfs*5), c.6201_6203delGCCins CCCA(p.Val2069Cysfs*14) and c.10705A > T (p.Lys3569*). In 52 families with positive results, 45 mothers (86.5%) showed positive results during carrier testing and de novo mutations arose in 7 probands. The prenatal diagnosis was offered to 34 fetuses whether the pregnant mother was a carrier or not. As a result, eight male fetuses were affected, three female fetuses were carriers, and the remaining fetuses had no pathogenic mutation. Conclusions This study reported that MLPA and NGS could be used for screening the DMD gene mutations. Furthermore, the stepwise procedure of prenatal diagnosis of DMD gene was shown in our study, which is important for assessing the mutation type of fetuses and providing perinatal care in DMD high-risk families.